2007
DOI: 10.1149/1.2720763
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition and Electrical Properties of SrTiO[sub 3] Thin Films Grown Using Sr(C[sub 11]H[sub 19]O[sub 2])[sub 2], Ti(Oi-C[sub 3]H[sub 7])[sub 4], and H[sub 2]O

Abstract: Atomic layer deposited SrTinormalO3 (STO) thin films were grown using Sr(normalC11normalH19normalO2)2 and Ti(Oi-normalC3normalH7)4 with a remote plasma activated or thermal normalH2O vapor as oxidant at growth temperatures ranging from 190to270°C . The as-grown films were amorphous and showed a low effective dielectric constant of ∼20 with a low leakage current density ( <10−7A∕cm2 at 1V ). The chemical binding status of the Sr ions varied with the degree of crystallization of the STO film. A reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 19 publications
0
66
0
Order By: Relevance
“…[15][16][17][18][19] The stoichiometry of the STO films strongly affects the crystallization temperature, crystalline microstructure after annealing and the dielectric constant. 20 Recent developments on ALD of STO showed that Sr-rich films have a smaller grain size after annealing resulting in lower leakage current values.…”
mentioning
confidence: 99%
“…[15][16][17][18][19] The stoichiometry of the STO films strongly affects the crystallization temperature, crystalline microstructure after annealing and the dielectric constant. 20 Recent developments on ALD of STO showed that Sr-rich films have a smaller grain size after annealing resulting in lower leakage current values.…”
mentioning
confidence: 99%
“…Hwang and coworkers used a 5 nm thick STO seed layer annealed at 650 1C for 1 min with RTA, which resulted in an improvement in the capacitance (2.7 mF cm À2 without a seed layer vs. 4.5 mF cm À2 with a seed layer) and a decrease in the J G (10 À1 A cm À2 without a seed layer vs. 10 À5 A cm À2 with a seed layer at 1 V) of the main STO layer. 86 They also reported a 3 nm thick STO seed layer annealed at 600-750 1C for 1 min with RTA. The capacitance of a 17 nm thick main STO layer significantly increased by a factor of 5.…”
Section: Seed Layer Schemementioning
confidence: 99%
“…In this section, we review characterization strategies that researchers have pursued to understand the morphology of thin-film perovskites and how they linked their findings to the obtained properties (Table 5). 15,46,[64][65][66]70,72,[76][77][78][79][80][81]83,[85][86][87]90,94,97,98,102,[104][105][106] To obtain compositional information, XPS is the most common technique. The information that can be obtained ranges from film contamination to the elemental composition within the topmost 1-10 nm of the film and its uniformity, chemical and electronic states, binding information, and depth information.…”
Section: Characterization Of Ultrathin Perovskite Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports on the growth of STO films by ALD from different volatile metal organic precursors at home built ALD systems [10,[12][13][14]. Whereas a broad variety of Ti precursors is available, for the ALD of the TiO 2 half cycle of strontium titanate, mainly precursors based on alkoxides and mixed alkoxides-diketonates like Ti( i OMe) 4 [15,16], Ti( i OPr) 4 [13,14] or Ti( i OPr) 2 (thd) 2 [17] are mentioned in the literature. Just recently, also cyclopentadienyl (Cp) based precursors like Cp*Ti(OMe) 3 [18] and (CpMe 5 )Ti(OMe) 3 [19] are described for the ALD of SrTiO 3 .…”
Section: Introductionmentioning
confidence: 99%